PENGARUH ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PEMASARAN MELALUI INOVASI SEBAGAI VARIABEL INTERVENING (Studi pada UMKM Batik di Jawa Tengah) - Gradistya, Giska Ova; Farida, Naili (Jurnal Ilmu Administrasi Bisnis, 2016)
This research was motivated by the increasing of SMEs omzet cause Batik development. Batik SMEs of Pati Regency and Semarang District are potential to thrieve but the sales is fluctuate and not achieving the sales target has been set. The purpose of this study was to determine the effect of market orientation and entrepreneurial orientation toward marketing performance through innovation in Batik SMEs of Central Java. Type of research is explanatory with data collection through questionnaires and interviews. Population is Batik SMEs of Pati Regency and Semarang District. Samples are 76 owners Batik SMEs of Pati District and Semarang Regency. Technique of sampling using saturated sampling or census This study uses quantitative analysis techniques using validity, reliability test, the correlation coefficient, simple and multiple regression analysis, the determination coefficient, significance test (t test) in one direction, regression 2 stages, and Sobel test using A.F. Hayes program. The results of the study are positive effect of market orientation and entrepreneurial orientation partially on innovation, and innovation positive effect to performance marketing. Regression analysis is known that the two stages of market orientation and entrepreneurial orientation influence on innovation with a coefficient of 0.166 and 0.739. Innovation on the performance of marketing at 0.464. Further Innovation acts as a partial mediating variable.